Contribution of Insurance in Economic Growth of Nepal - Pant, Srijana; KC, Fatta Bahadur (Journal of Advanced Academic Research, 2018)
Insurance as a risk transfer mechanism may contribute to economic growth of a country by fostering long term investment through capital that is collected from accumulated savings from individuals. The main objective of this paper is to examine the contribution of insurance in economic growth of Nepal using determinants of insurance like total insurance premium, Life insurance premium, Non-life insurance premium, employment and investment using data from 2004 to 2015 based on theoretical and empirical evidence. Fortunately, in past few years, lots of research has been done to map the specific contributions made by insurance sector in economic growth of the country applying theoretical and empirical evidence. The evidence suggests that insurance may contribute to economic growth by creating investment climate and managing risk in more efficient way. Theoretically, the studies show insurance has a positive contribution to different levels of development and further suggests to examine the relationship between insurance and economic growth using appropriate model.